Prevalence of Depression among Adults Residing in A Coastal Area of Thiruvananthapuram District, Kerala - Divija Pillai; Anil Bindhu S; Manju L; Susanna J; Jeesha Haran (Medsci Publications, 2019)
Introduction: Depression is an important public health problem. The National Mental Health Survey (NMHS) 2015-16 of India re- ports that the current prevalence of depression is 2.7%. Objective: To estimate the prevalence of depression among adults living in a coastal area of Trivandrum district. To find the factors associated with depression among adults living in a coastal area of Trivandrum district. Materials and methods: A cross sectional study was carried out in two wards of Anchuthengu, a coastal area in Trivandrum district. The sample size obtained was 855. Patient Health Questionnaire (PHQ)-9 was used to assess depression, the data  was entered in MS Excel and was analyzed using SPSS version 16. Results: Majority of the participants had minimal depression 85.5% (84.1 -88.9), mild depression 5.5% (4.0 -7.1), moderate 4.6% (3.2 - 6.0) , moderately severe 2.5% (1.5 -3.6) and severe 0.9% (0.4 - 1.6). Married status, mental illness in family, presence of financial burden and belonging to BPL family were found to be associated with depression. Conclusion: Proper treatment and counselling for depressed indi- viduals and health education in community is necessary in order   to address this problem.